Preponderance of inhibitory versus excitatory intramuscular nerve fibres in human chagasic megacolon - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel (International Journal of Colorectal Disease, 2012)
Introduction: Megacolon, chronic dilation of a colonic segment, is a frequent sign of Chagas disease. It is accompanied by an extensive neuron loss which, as shown recently, results in a partial, selective survival of nitrergic myenteric neurons. Here, we focused on the balance of intramuscular excitatory (choline acetyltransferase [ChAT]-immunoreactive) and inhibitory (neuronal nitric oxide synthase [NOS]- as well as vasoactive intestinal peptide [VIP]-immunoreactive) nerve fibres. Materials and methods: From surgically removed megacolonic segments of seven patients, three sets of cryosections (from non-dilated oral, megacolonic and non-dilated anal parts) were immunhistochemically triple-stained for ChAT, NOS and VIP. Separate area measurements of nerve profiles within the circular and longitudinal muscle layers, respectively, were compared with those of seven non-chagasic control patients. Additionally, wholemounts from the same regions were stained for NOS, VIP and neurofilaments (NF). Results: The intramuscular nerve fibre density was significantly reduced in all three chagasic segments. The proportions of inhibitory (NOS only, VIP only, or NOS/VIPcoimmunoreactive) intramuscular nerves were 68 %/58 % (circular/longitudinal muscle, respectively) in the controls and increased to 75 %/69 % (oral parts), 84 %/76 % (megacolonic) and 87 %/94 % (anal) in chagasic specimens. In the myenteric plexus, NF-positive neurons co-staining for NOS and VIP also increased proportionally. The almost complete lack of dendritic structures in ganglia of chagasic specimens hampered morphological identification. Discussion and conclusion: We suggest that preponderance of inhibitory, intramuscular nerve fibres may be one factor explaining the chronic dilation. Since the nerve fibre imbalance is most pronounced in the anal, non-dilated segment, other components of the motor apparatus (musculature, interstitial cells, submucosal neurons) have to be considered. © Springer-Verlag 2012.
Keywords: Chagasic megacolon; Enteric nervous system; Neurodegeneration; Neuronal nitric oxide synthase; Vasoactive intestinal peptide